PERKEMBANGAN EKONOMI DAN PERBANKAN PROPINSI JAWA TENGAH TAHUN 2004 - Amril Arief (Journal of Indonesian Economy and Business (JIEB), 2005)
Central Java’s economy in 2004 has a higher economic growth and inflation than 2003.Economic growth on supply side was influenced by three economic sectors (trade, hotel &restaurant, manufacturing industry, and services). On demand side, economic growth wasinfluenced by private consumption, government consumption, and export. The priordeterminance of inflation in 2004 is come from supply side: volatile foods and clothes (cost push inflation). On demand side, inflation was influenced by communication and financial services. Banking sector (commercial bank and rural bank) has a good performance in 2004. All of banking performance indicators were increased, i.e. total asset, total deposit, credit, and loan to deposits ratio. Meanwhile, ratio of non performing loans was declined.Central Java’s export in 2002-2004 has increased significantly that be dominated byfour prime industries (textile, furniture, wearing apparel, and products of wood). Thecontribution of four industries is 76,04% of total export. Businessmen and exporters havebeen understood that high level competitiveness of the export commodities is majorprecondition to compete in international market. This awareness makes optimism spirit ofbusinessmen to increase Central Java’s export performance.Outlook of Central Java’s economy in 2005 is predicted will have a higher economicgrowth with higher inflation than 2004. Two dominant economic sectors (manufacturingindustry sector and trade, hotel & restaurant sector) will lead its growth on supply side.Private consumption, investment, and export will be a prime mover of growth on demandside. The administered price, especially increasing of oil (BBM) price, will be a priordeterminance of inflation in 2005. Outlook of banking sector, especially on credit, also hasa good prospect. This is based on increasing trends of real sector and household needs,stability of social and political condition, and infrastructure projects of central governmentthat will be supported by banking sector. Outlook of Central Java’s export in 2005 isdepend on performance of export commodities of four industries above. To realize it,regional government of Central Java must create an export development program focusing on product quality improvement. Meanwhile, the linked institutions (public and private institutions) on export development must cooperate on implementing and sustainable program to realize an effective synergism.